2018
DOI: 10.1016/j.jvs.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microbiome-modulated indole- and phenyl-derived metabolites associate with advanced atherosclerosis and postoperative outcomes

Abstract: Specific microbe-derived metabolite signatures associate with advanced human atherosclerosis and postoperative cardiac complications. We suggest that these metabolites are potential novel biomarkers for atherosclerotic disease burden and that further investigation into mechanistic links between defined microbial metabolic pathways and cardiovascular disease is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 71 publications
9
90
2
3
Order By: Relevance
“…In clinical investigations, IDO activity has been reported to be positively correlated with a range of atherosclerosis risk factors in the female population, including LDL-C (Pertovaara et al, 2007). Concerning the indole pathway, tryptophan, indole-3-propionic acid, and indole-3-aldehyde were shown to be decreased in atherosclerotic patients, while kynurenine/tryptophan ratios were increased (Cason et al, 2018); still, no independent correlation with cholesterol has yet been reported. In conclusion, the scarcity of studies does not allow the indole pathway to be implicated in regulation of cholesterolemia ( Figure 2).…”
Section: Diet-associated Tryptophan (Trp) Derivativesmentioning
confidence: 97%
“…In clinical investigations, IDO activity has been reported to be positively correlated with a range of atherosclerosis risk factors in the female population, including LDL-C (Pertovaara et al, 2007). Concerning the indole pathway, tryptophan, indole-3-propionic acid, and indole-3-aldehyde were shown to be decreased in atherosclerotic patients, while kynurenine/tryptophan ratios were increased (Cason et al, 2018); still, no independent correlation with cholesterol has yet been reported. In conclusion, the scarcity of studies does not allow the indole pathway to be implicated in regulation of cholesterolemia ( Figure 2).…”
Section: Diet-associated Tryptophan (Trp) Derivativesmentioning
confidence: 97%
“…Была найдена обратная корреляция с прогрессирующим атеросклерозом для индола, индол-3-пропионовой кислоты и концентрации индол-3-альдегида, в то время как для соотношения кинуренина к триптофану -положительная корреляция. При многофакторном анализе соотношение кинуренин−триптофан достоверно ассоциировалось с послеоперационными кардиальными осложнениями (отношение шансов 44,1; 95% доверительный интервал 3,3−587,1; р=0,004) [26].…”
Section: сердечно-сосудистые заболеванияunclassified
“…Since medical researchers have focused on the metabolic products of human multisliced colonizing microbiota film, a new interesting scenario has been proposed. The role of metabolites in host inflammatory process modulation and, consequentially, in atherosclerotic clinical manifestations as PAD has been defined to be much more essential and incisive than the producing microbe itself [145, 146].…”
Section: The Metabolome: From Waste To Biomarkermentioning
confidence: 99%
“…An increasing number of studies enrich the knowledge about the gut metabolome by studying tryptophan (trp), kynurenine/tryptophan (kyn/trp) ratio, indole sulfonate, p-cresyl sulfonate (PCS), hippuric acid (HA), indole-3-carboxaldehyde (i3a), indole 3-proprionic (i3p), H 2 S, and phenylacetylglutamine and their influence on atherosclerotic phenomenon [147], like PAD in patients affected by a high grade of severe atherosclerosis, an end-stage disease characterized by an hemodynamic stenosis of carotid arteries aimed at an endarterectomy, disabling claudication, or critical limb ischemia undergoing an endovascular revascularization procedure or “demolitive” surgery with amputation in nonsolvable PAD [145]. Specifically, the tryptophan depletion determines an overactivation of the transduction signal of a stress pathway [145, 148] and an elevated value of the kyn/trp ratio is found in inflammatory statements, including infections with a proven positive relation to MACE. In addition, a low value of the kyn/trp ratio has been observed in germ-free mice with an interesting opposite tendency of this relation in case used for the first colonization of the same mice [145, 149, 150].…”
Section: The Metabolome: From Waste To Biomarkermentioning
confidence: 99%
See 1 more Smart Citation